African experience of time and its compatibility with the Old Testament view of time as suggested in the genealogy of Genesis 5 - De Wet Oosthuizen, Rudolph (Old Testament essays, 1993)
Traditionally, interpretations of Genesis 5 have focused on questions asked of the text as determined by a Western worldview - for example, the approaches of historical criticism and science of literature, to mention two main perspectives. A reading of the text from a perspective informed by our own context, Africa, sheds some new light on the theological understanding of the genealogy in Genesis 5 in that it allows the biblical and African views of reality to interact in the process of interpretation towards a more inteffal and wholesome understanding of the human situation.